Analisis Karakteristik Obligasi terhadap Return Obligasi pada Sub Sektor Perbankan Tahun 2010-2013 - Herlambang, Resandy; Nuryartono, Nunung (Jurnal Aplikasi Manajemen, 2016)
Abstract: Corporate bond markethas dominated by banking sub-sector. This bond issue canÂ not be separated for strengthening the capital structure of banking sub-sectoritself. Meanwhile, the net interest margin has decreased over the last few years, it will affect to their profit. This study aims to analyze the characteristics of bonds play an important role in influencing the return of the bonds on the banking sub-sector. Data were processed by using panel data, which consists of 14 bonds and using quarterly data from 2010â€“2013. According to the results of Hausman test, this study uses the random effect method. The results showed that the yield to maturity, interest rate, and duration had a significant influence on the bond return, while the bond rating and debt to equity ratio do not have effect on bond return.